(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
This article focuses on the background of the Mexican cultural magazine Nexos and on the first four years of its existence, in which the historian Enrique Florescano served as its director (1978-1982). Taking as a premise the fact that magazines are spaces with their own characteristics and dynamics and, at the same time, spaces that condense, materialize and express certain historical processes, this text moves on two levels. On the one hand, it studies the particular development of the magazine and the network of individuals that was formed around it from multiple sources, giving a preponderant place to interviews with the protagonists. On the other, the political, cultural and social context that made its emergence possible and shaped some of its main features is analyzed.